Change or continuity? Exploring post-revolution state - building in Ukraine and Armenia - Aram Terzyan (CES Working Papers, 2020)
The paper focuses on the post-Maidan and post-Velvet Revolution state-building in Ukraine and Armenia. Examining the cases of Ukraine and Armenia, the qualitative, comparative analysis presented in this paper uncovers some of the similarities and differences between the two post-Soviet revolutions in terms of their political and economic implications. The study suggests that, while the revolutions have given a strong impetus to political and economic reforms in oligarchy-driven and corruption-stricken Ukrainian and Armenian societies, the path to ultimate success involves overcoming the authoritarian legacy and developing democratic institutions. The analysis of the relationship between domestic change and foreign policy shows that in contrast to Ukraine, where the 'choice for Europe' was the core rationale behind the Euromaidan, the domestic change in Armenia has not led to foreign policy shifts. Nevertheless, this study avoids reductionist explanations of external drivers of change. Rather, it treats the domestic actors as the key agents to transform the economic and political landscapes of the two post-Soviet countries.
Keywords: 330; Ukraine; Armenia; "Velvet Revolution"; Maidan Revolution; state-building; democracy consolidation